Edukasi Screen Time pada Anak di Masyarakat Kota Tasikmalaya - Husna, Hanna Nurul; Izfadllillah, Thesa; Wardani, Gatut Ari; Pratama, Azril; Rahma, Aisyah Alpiah; Micola, Muhammad Yolanda (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2023)
Changes in the behavior patterns of people who are accustomed to online activities can have positive and negative impacts on the body, especially children eyes. However, not many people know this. Therefore, community service activities are carried out which aim to provide education about screen time in book form. The book was made using the Canva application which contains material regarding the meaning of screen time, the working principles of screens and blue light, the positive and negative effects of blue light, rules for using devices, and recommendations for treatment for parents. Then counseling was carried out in the form of distribution of books and education to Orphanages, PAUD, Kindergartens and Elementary Schools in Tawang District, Tasikmalaya City. This activity can have a good impact on the community regarding the importance of limiting screen time to maintain eye and body health.